Empowering indigenous communities through participation in tourism - Nur Aliah, M; Mazne, I.; Siti Atikah, Rusli *; Derweanna, B. S.; Nurul Fardila, A. R.; Harnidah, S.; Nurashikin, A. R.; Nur Azimah, O. (Inderscience, 2019)
This study explores the involvement of Malaysian indigenous peoples (Orang Asli) at both the individual and community level to analyse the impact of tourism development on the economic and socio-cultural aspects of their communities. The study was conducted at two tourism sites, Bukit Tadom and Cameron Highlands. Semi-structured interviews were conducted with 14 participants from the Orang Asli community and Orang Asli employees and management at the sites. Data were thematically analysed. Orang Asli communities recognised the opportunities that tourism development brings to their social and economic conditions, although it is not wholly beneficial. They also want to be actively involved in tourism planning. The study contributes to the development of indigenous peoples, especially in Malaysia, promoting a new perspective on long-term tourism development. It also highlights several new considerations that should be addressed by the authority in planning and managing tourism sites, especially in regard to community acceptance, involvement and demand for benefits.